Laparoscopic Living donor liver transplantation in irresectable intrahepatic cholangiocarcinoma in primary sclerosing cholangitis associated liver cirrhosis - Bednarsch, Jan; Lang, Sven A.; Heise, Daniel; Strnad, Pavel; Neumann, Ulf P.; Ulmer, Tom F. (Zeitschrift für Gastroenterologie, 2024)
Intrahepatic cholangiocarcinoma (iCCA) is the second most common primary liver tumor and usually associated with a poor oncological prognosis. The current gold standard is the surgical resection of the tumor with subsequent adjuvant therapy. However, in case of irresectability e.g. in case of liver cirrhosis, a palliative treatment regime is conducted.This report demonstrates the case of an irresectable iCCA in liver cirrhosis due to primary sclerosing cholangitis (PSC) treated by living-donor liver transplantation (LDLT) facilitated by minimal invasive donor hepatectomy. No postoperative complications were observed in the donor and the donor was released on the 6th postoperative day. Further, after a follow-up of 1.5 years, no disease recurrence was detected in the recipient.According to the recent international literature, liver transplantation can be evaluated in case of small solitary iCCA (< 3 cm) in cirrhosis. Less evidence is provided for transplantation in advanced tumors which are surgically not resectable due to advanced liver disease or infiltration of major vessels, however some reports display adequate long-term survival after strict patient selection. The selection criteria comprise the absence of distant metastases and locoregional lymph node metastases as well as partial remission or stable disease after neoadjuvant chemotherapy. Due to no established graft allocation for iCCA in Germany, LDLT is currently the best option to realize transplantation in these patients. Developments in the last decade indicate that LDLT should preferentially be performed in minimal invasive manner (laparoscopic or robotic) as this approach is associated with less overall complications and a shorter hospitalization. The presented case illustrates the possibilities of modern surgery and the introduction of transplant oncology in the modern therapy of patients combining systemic therapy, surgical resection and transplantation to achieve optimal long-term results in patients which were initially indicated for palliative treatment.
Keywords: cholangiocarcinoma; chemotherapy; liver transplantation; living donor liver transplantation